The link between morphosyntactic accuracy and textbook presentation: The morphosyntax of subject‐verb agreement in Arabic. (18th October 2018) - Azaz, Mahmoud
Abstract : The acquisition of morphosyntax presents challenges for learners of all second/foreign languages. This cross‐sectional study investigated English‐speaking learners' morphosyntactic accuracy in the symmetrical subject‐verb agreement type (in subject‐initial sentences) and in the asymmetrical subject‐verb agreement type (in verb‐initial sentences) in Arabic. In addition, it examined the extent to which their accuracy rates were reflected in implicit exposure to and explicit presentation of those structures. The results of a prompted production task showed that first‐, second‐, and third‐year learners exhibited low morphosyntactic accuracy rates only in the asymmetrical type. In addition, the production of Group 2 (second‐year) and Group 3 (third‐year) was patterned after that of Group 1 (first‐year) in the symmetrical type but exhibited greater variation in the asymmetrical type. Implications for explicit textbook presentation and instruction of morphosyntactic intricacies are discussed. The Challenge: In many foreign language contexts, learners are faced with the task of learning morphosyntactic intricacies. To what extent do accuracy rates of learners at different course levels vary in mastering these intricacies? To what extent can these accuracy rates be linked to implicit exposure to and explicit textbook presentations of these intricacies?